O uso do software geogebra 3D no ensino da geometria espacial - Leite, Emiliano Sousa (2020)
This work explores the use of information and communication technology through the educational software GeoGebra 3D in spatial geometry, which is used mainly for the construction, visualization and understanding of geometric figures. The general objective of this research is to find ways to make the teaching of spatial geometry more dynamic and to assist in the learning of mathematics. Research shows that technical resources have the potential to assist in the geometry teaching process. As a specific objective, the study resolves a construction of geometric figures through the concepts of perimeter, horizontal and total area and volume, in order to seek the development of spatial thinking. A major challenge is to arouse students' curiosity and stimulate interest in research carried out through the use of educational software, which is an important tool, so that a classroom becomes more applicable and explanatory. The main characteristic of the development of this work is the dynamics provided by the educational software, which contributes to the teaching of Geometry, thus expanding the possibilities of spatial reasoning.